Criminal Sanctions Against Theft With Violance - Ni Made Trisna Dewi (Dwijendra University, 2022)
Talking about theft with violence, whether it concerns the case, its impact, or the relationship between the perpetrator and the victim of the crime must be based on and have a background in social, cultural, economic, and community structures. The type of research used in this research is normative research. Based on the discussion in the previous chapters, several conclusions can be drawn, namely: 1) Evidence of the elements of the criminal act of theft with violence, in this case it has provided the achievements of the applicable law, both in the handling process to the investigation and decision or punishment. imprisonment according to the mandate in Article 365 of the Criminal Code. Regarding theft which is preceded, accompanied or followed by violence or threats of violence, with the threat of imprisonment for fifteen years. 2) The provision of criminal sanctions against perpetrators of theft with violence above, in terms of giving this sanction, is based on the results of evidence from the elements of the criminal act of theft with violence, as has been done by investigators or law enforcement to give a verdict or punishment. to the perpetrator in accordance with Article 365 of the Criminal Code with a prison sentence of 15 years in prison.